Β‐Caryophyllene induces apoptosis and inhibits cell proliferation by deregulation of STAT‐3/mTOR/AKT signaling in human bladder cancer cells: An in vitro study. Issue 10 (28th July 2021) - Yu, Xiaodong; Liao, Bo; Zhu, Pingyu; Cheng, Shulin; Du, Zhongbo; Jiang, Guo
Abstract: The current study aimed to explore the antitumor effect of β‐caryophyllene (BCP) on two different cell lines of T24 and 5637 human bladder cancer (BC) cells and its potential molecular mechanisms in inhibition of STAT‐3/mTOR/AKT signaling pathways and the inductive process of apoptosis mechanism. The results indicated that BCP showed significant cytotoxicity in BC T24 and 5637 cells in a dose‐ and time‐dependent manner, and IC50 values were 40 µg/ml in the BC cells T24 and 5637. Reactive oxygen species (ROS) synthesis and apoptosis induction were significantly developed, but the mitochondrial membrane potential (Δψm) decreased on BCP treatment as detected by the fluorescence method. Moreover, cell migration was markedly reduced in BCP and Bax, Bcl‐2 mRNA expression was modified. Finally, it was found that the STAT‐3, mTOR, and AKT protein expressions were suppressed via inhibition of cytotoxicity in T24 and 5637 cells. Therefore, we finally concluded that BCP is an effective treatment against BC T24 and 5637 cells, and it has great chemotherapeutic potential for further bladder carcinoma treatment.